Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 18)
"Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 18)" [g0973018.jpg], n.d.